2017
DOI: 10.1007/s10916-017-0785-5
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Classifier to Support Diagnose Meningitis in Less Developed Areas of Brazil

Abstract: This paper describes the development of statistical classifiers to help diagnose meningococcal meningitis, i.e. the most sever, infectious and deadliest type of this disease. The goal is to find a mechanism able to determine whether a patient has this type of meningitis from a set of symptoms that can be directly observed in the earliest stages of this pathology. Currently, in Brazil, a country that is heavily affected by meningitis, all suspected cases require immediate hospitalization and the beginning of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This section summarises the construction process of our three decision models, described in detail in [42], [43]. Decision Model 1 (DM1) determines, only in terms of observable symptoms, whether or not the patient has meningitis; Decision Model 2 (DM2), using the same input symptoms, predicts the probability of having meningococcal meningitis; and finally, Decision Model 3 (DM3) explores the aetiology of the disease employing some chemical and cytological test data.…”
Section: ) Decision Models Constructionmentioning
confidence: 99%
“…This section summarises the construction process of our three decision models, described in detail in [42], [43]. Decision Model 1 (DM1) determines, only in terms of observable symptoms, whether or not the patient has meningitis; Decision Model 2 (DM2), using the same input symptoms, predicts the probability of having meningococcal meningitis; and finally, Decision Model 3 (DM3) explores the aetiology of the disease employing some chemical and cytological test data.…”
Section: ) Decision Models Constructionmentioning
confidence: 99%
“…However, the traditional diabetes screening method needs an expensive blood test and extra manpower, which is a big challenge for the backward remote areas [ 8 ]. A diabetes screening model built by easily available indicators, without expensive examinations, is crucial to the occurrence and development of diseases [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main challenge in screening for diabetes is economic, including expensive blood work and additional human labor, which is even more challenging in developing countries [6]. The World Health Organization recommends that simple strategies should be developed to identify patients with risk for diabetes and then implement early lifestyle interventions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Developing appropriate disease prediction algorithms can be technically challenging. In a Brazilian investigation, Lélis et al [6] applied seven classification techniques to make a diagnosis of meningococcal meningitis and demonstrated this model is accurate and affordable. Choi et al [8] developed two models to screen for prediabetes of 9251 individuals using an artificial neural network (ANN) and support vector machine (SVM) and performed a systematic evaluation of the models using internal and external validation, and concluded that the SVM model is superior to the ANN model in the screening for prediabetes.…”
Section: Introductionmentioning
confidence: 99%